Experience of Parents on Seeking Basic Immunization Program during The Situation of The Coronavirus Outbreak (COVID-19) - lohmae, userow; Kajornkittiya, Khemmapat; Dowrote, Nutsara; Wansa-aree, Raimee; Cheni, Rusnee (Journal of The Royal Thai Army Nurses, 2023)
This qualitative research aimed to study parents’ experience seeking basic immunization programs during the coronavirus outbreak (COVID-19). The survey collected data from 12 Parents of children aged 1 - 5 years to receive basic immunizations in the Health Promoting Hospital Health Center 12. The data were collected through in-depth interviews. The data were analyzed by transcribed verbatim and content analysis. The results showed that the parents’ experience in seeking basic immunization programs during the coronavirus outbreak (COVID-19) had divided into 2 main points (1) Factors promoting the adoption of children for vaccination are the perception of the child’s vaccination, obtaining information, and family involvement, and (2) the factors impeding children to receive vaccination are illness, disease outbreaks and relocation of parents. The results of this study can be used as a guideline for developing a model for promoting parents in bringing their children to receive basic immunizations on an ongoing basis. providing information about the importance of vaccination, caring for symptoms after vaccination, and having an alert system when vaccination is due encourages to receive comprehensive vaccinations according to their age and reduces the chances of disease in children.